Developing An Achievement Test in Learning of Physics for Assessment - Dhien, A.; Kumaidi, K. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
The aims of the study are to know the advantage of achievement test in learning physics developed by utilizing item specifications and the ability distribution of tenth grade students at senior high school in Yogyakarta. The benefits of the research are to prepare test items, provide guidelines for teachers in writing quality items and produce learning achievement test that can be used on School Exams. This research is developmental research used the model suggested by Oriondo&Dallo-Antonio. The subjects were tenth grade students. The limited test was tried out to 354 students in school with categories of high, medium and low. The wide scale test was tried out to 644 students on package A and package B. Item analysis was conducted by using qualitative and quantitative analysis. This research shows developed test in physics by utilizing item specifications had the advantage in producing more equate test the ability distributions of tenth grade students at senior high school in Yogyakarta were mostly at the average category.